Land Titling and Rural Transition in Vietnam - Do, Quy-Toan (2012)
We examine the impact of the 1993 Land Law of Vietnam, which gave households the power to exchange, transfer, lease, inherit, and mortgage their land-use rights. We use household surveys before and after the law was passed, together with the considerable variation across provinces in the speed of implementation of the reform, to identify the impact of the law. We find that the additional land rights led to statistically significant increases in the share of total area devoted to long-term crops and in labor devoted to nonfarm activities. However, these changes are not large in magnitude and appear to be driven mainly by the increased security of tenure provided by the law rather than by increased access to credit markets or greater land market participation.